Hubungan China dan Taliban dalam Konflik Bersenjata Di Afghanistan - Syafira, Sisilia Putri; Yumitro, Gonda (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
This article discusses the relationship between the Taliban and China in the Afghan conflict. This research is a qualitative type, the references used are news, journal articles, official government websites, and the Mendeley library. In collecting data, the author will use the Harzing Publish or Perish application, which is then processed using Vosviewer. This study uses a complex interdependence concept approach. The study found that it was China's presence in Afghanistan after the Taliban rule that seemed to be more prominent than other countries. Furthermore, there is the intensity of relations between China and the Taliban in the armed conflict in Afghanistan. With the Complex Interdependence approach, it is found that China and the Taliban have security and economic dependencies. China is seeking to extend legitimacy to the Taliban in its new leadership in Afghanistan. Then in anticipating the reoccurrence of the conflict in Afghanistan, China is trying to balance its diplomacy against the Afghan government and the Taliban